Analysis of bulletproof performance of structurally optimized ceramic composite armor through numerical simulation and live fire test - Zhiyong Chen; Jian Hou; Fei Gao; Sier Deng; Yingqiang Xu; Jing Qin; Shuaishuai Cui; Jun-Hyun Kim (Scientific Reports)
Abstract This work aims to address key issues in the ballistic performance of ceramic-based composite armor, particularly at the joints of spliced ​​bulletproof panels. The edge structure of C/C-SiC ceramic plates and ultra-high molecular weight polyethylene is redesigned to superimpose the joint areas. These structurally optimized composite pads are examined by numerical simulation of impact dynamics to understand their anti-penetration performance whose accuracy is then validated by live fire tests. The results reveal that (1) the ceramic plates with improved edge design enhance the anti-penetration efficiency, (2) the established dynamic constitutive model of penetration resistance effectively predicts the ballistic performance of the armor pad, and (3) inability to penetrate high-speed real bullets through the armor suggests that the ballistic performance fully meets the protection requirements of the MIL-A-46103EIII Class 2 A standard. In this regard, structural regulation of the shape of the ceramic-based composite plates allows for the design of lightweight armor with improved bulletproof capability.